Solarpv-revb: sustainable energy storage technology for rural electrification using second-life batteries - Kamarzaman, Nur Atharah; Sulaiman, Shahril Irwan; Zainuddin, Hedzlin; Ibrahim, Rahayu (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
SolarPV-REVB (Retired Electric Vehicle Battery) is an innovative energy storage technology that utilizes retired electric vehicle batteries (REVBs) to power stand-alone photovoltaic (SAPV) systems. This approach addresses three significant issues, which are SAPV system reliability, cost of energy storage and environmental sustainability. SolarPV-REVB assures optimal system performance by integrating second-life battery in SAPV system design which balances system reliability and cost-effectiveness. The aim of the project is to repurpose electric vehicle batteries as energy storage and to enhance the SAPV system’s reliability and cost. This approach positively impacts both the socioeconomic and environmental landscapes by minimizing battery waste, lowering energy costs, and boosting off-grid communities' access to sustainable electricity. SolarPV-REVB encourages the circular economy, renewable energy usage, and technology innovation. Its reliability, cost competitiveness, and environmental benefits offer major commercialization opportunities, making it an appealing solution for remote energy applications. This system solves global energy storage concerns by developing a sustainable approach and significantly provides solutions for renewable energy systems